Legislación y protección contra el abandono de personas adultas mayores: un análisis comparativo y propuestas para el marco jurídico en Ecuador - Morla Cotto, Adrián Valentín (2024)
The rights of older adults are fundamental to guarantee their dignity, well-being and active participation in society. The history of these rights dates back to the Universal Declaration of Human Rights of 1948, which recognizes the right to dignity, equality and non-discrimination for all people, including older adults. Subsequently, in 1991, the United Nations General Assembly proclaimed the "United Nations Principles for Older Persons", which establish the fundamental rights of older persons, such as the right to independence, participation, care, self-development, equality and non-discrimination. In many countries, specific laws and policies have been enacted to protect the rights of older adults, addressing issues such as access to health care, adequate housing, social security, participation in community life, protection against abuse and discrimination, among others. These antecedents have laid the foundations for the recognition and protection of the rights of older adults worldwide, and continue to be the subject of attention and development in the legislation and policies of many countries. Based on the realities that are experienced (suffered) in these times, where youth do not have respect or consideration for our older adults, both due to generational change, the discipline and good customs instilled in homes, and due to the lack of an exemplary punishment towards people who violate the integrity of our older adults, whether physically or psychologically. With this premise we base this project, aimed at the Protection against abandonment and abuse of older people, we will also carry out a comparative analysis with existing laws in other countries that have advanced the issue and we will present proposals for the Legal Framework in Ecuador.